Is Concurrent Training Efficacious Antihypertensive Therapy? A Meta-analysis. Issue 12 (December 2016) - CORSO, LAUREN M. L.; MACDONALD, HAYLEY V.; JOHNSON, BLAIR T.; FARINATTI, PAULO; LIVINGSTON, JILL; ZALESKI, AMANDA L.; BLANCHARD, ADAM; PESCATELLO, LINDA S.
ABSTRACT: N/A: Aerobic exercise training and, to a lesser degree, dynamic resistance training, are recommended to lower blood pressure (BP) among adults with hypertension. Yet the combined influence of these exercise modalities, termed concurrent exercise training (CET), on resting BP is unclear. Purpose: This study aimed to meta-analyze the literature to determine the efficacy of CET as antihypertensive therapy. Methods: Electronic databases were searched for trials that included the following: adults (>19 yr), controlled CET interventions, and BP measured pre- and postintervention. Study quality was assessed with a modified Downs and Black Checklist. Analyses incorporated random-effects assumptions. Results: Sixty-eight trials yielded 76 interventions. Subjects ( N = 4110) were middle- to older-age (55.8 ± 14.4 yr), were overweight (28.0 ± 3.6 kg·m −2 ), and had prehypertension (systolic BP [SBP]/diastolic BP [DBP] = 134.6 ± 10.9/80.7 ± 7.5 mm Hg). CET was performed at moderate intensity (aerobic = 55% maximal oxygen consumption, resistance = 60% one-repetition maximum), 2.9 ± 0.7 d·wk −1 for 58.3 ± 20.1 min per session for 19.7 ± 17.8 wk. Studies were of moderate quality, satisfying 60.7% ± 9.4% of quality items. Overall, CET moderately reduced SBP ( d b = −0.32, 95% confidence interval [CI] = −0.44 to −0.20, −3.2 mm Hg) and DBP ( d b = −0.35, 95% CI = −0.47 to −0.22, −2.5 mm Hg) versus control ( P < 0.01). However, greater SBP/DBP reductions were observed among samples with hypertension in trials of higher study quality that also examined BP as the primary outcome (−9.2 mm Hg [95% CI = −12.0 to −8.0]/−7.7 mm Hg [95% CI = −14.0 to −8.0]). Conclusions: Among samples with hypertension in trials of higher study quality, CET rivals aerobic exercise training as antihypertensive therapy. Because of the moderate quality of this literature, additional randomized controlled CET trials that examine BP as a primary outcome among samples with hypertension are warranted to confirm our promising findings. Abstract : Supplemental digital content is available in the text.